Controlled release of antimicrobial Cephalexin drug from silica microparticles - Rao, B. V. Bhaskara; Mukherji, Ruchira; Shitre, G.; Alam, F.; Prabhune, Asmita; Kale, Sangeeta N. (Materials Science & Engineering C-Materials for Biological Applications, 2014)
Release of antimicrobial drugs in a controlled fashion for extended duration of time has been investigated for long. Such controlled-drug-releasing materials show promising applications in medicinal bandages. Along with antimicrobial agents, one could also incorporate other therapeutic drugs, to make such bandages more versatile. In this context, silica micro particles were synthesized using direct reduction method, in which the synthesis was done in the presence of Cephalexin. Cephalexin was chosen as an antimicrobial candidate. The morphological characterization shows formation of monodispersed, silica microparticles of similar to 200 nm in size. The FTIR spectroscopy shows weak interaction of the drug molecule at its hydroxide (OH) site with oxygen ions on the silica surface. Upon conjugation, the UV-vis spectroscopy shows persistence of the Cephalexin signature, especially its R group, confirming its antimicrobial activity even after conjugation. Loading studies reveal 12% Cephalexin loading on silica. The antimicrobial studies were done on three micro-organisms, namely, Staphylococcus aureus, Bacillus subtilis and Escherichia coli. Using zone-of-inhibition studies, it was found that E. coli, did not respond to the delivery of Cephalexin either directly or via microparticles. However, for both S. aureus and B. subtilis, the particles showed controlled release of Cephalexin for the duration of 48 h and continued maintenance and even increase in the zone of inhibition. This work demonstrates an effective protocol to prepare antimicrobial patches for controlled drug delivery. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial; Medicinal bandage; Silica microparticles; sustained drug release

Single-layer graphene-assembled 3D porous carbon composites with PVA and Fe3O4 nano-fillers: an interface-mediated superior dielectric and EMI shielding performance - Rao, B. V. Bhaskara; Yadav, Prasad; Aepuru, Radhamanohar; Panda, H. S.; Ogale, Satishchandra; Kale, S. N. (Physical Chemistry Chemical Physics, 2015)
In this study, a novel composite of Fe3O4 nanofiller-decorated single-layer graphene-assembled porous carbon (SLGAPC) with polyvinyl alcohol (PVA) having flexibility and a density of 0.75 g cm(-3) is explored for its dielectric and electromagnetic interference (EMI) response properties. The composite is prepared by the solution casting method and its constituents are optimized as 15 wt% SLGAPC and 20 wt% Fe3O4 through a novel solvent relaxation nuclear magnetic resonance experiment. The PVA-SLGAPC-Fe3O4 composite shows high dielectric permittivity in the range of 1 Hz-10 MHz, enhanced by a factor of 4 as compared to that of the PVA-SLGAPC composite, with a reduced loss by a factor of 2. The temperature dependent dielectric properties reveal the activation energy behaviour with reference to the glass transition temperature (80 degrees C) of PVA. The dielectric hysteresis with the temperature cycle reveals a remnant polarization. The enhanced dielectric properties are suggested to be the result of improvement in the localized polarization of the integrated interface system (Maxwell-Wagner-Sillars (MWS) polarization) formed by the uniform adsorption of Fe3O4 on the surface of SLGAPC conjugated with PVA. The EMI shielding property of the composite with a low thickness of 0.3 mm in the X-band (8.2-12.4 GHz) shows a very impressive shielding efficiency of similar to 15 dB and a specific shielding effectiveness of 20 dB (g cm(-3))(-1), indicating the promising character of this material for flexible EMI shielding applications.